1999
DOI: 10.21273/jashs.124.6.690
|View full text |Cite
|
Sign up to set email alerts
|

1-Methylcyclopropene Inhibits Apple Ripening

Abstract: An ethylene action inhibitor, MCP, was applied to preclimacteric and climacteric apple [Malus sylvestris L. (Mill.) var. domestica Borkh. Mansf.] fruit. Experiments were conducted in North Carolina and Washington State utilizing the following cultivars: Fuji, Gala, Ginger Gold, Jonagold, and Delicious. MCP inhibited loss of fruit firmness and titratable acidity when fruit were held in storage at 0 °C up to 6 months and when fruit were held at 20 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
123
0
24

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(176 citation statements)
references
References 6 publications
29
123
0
24
Order By: Relevance
“…Samples from every treatment were taken at intervals for fruit firmness assay. Bars indicate standard deviation of the mean (n = 6) Plant Growth Regul (2009) 57:185-192 187 inhibited by 1-MCP (Fan et al 1999;Dong et al 2002;Ergun et al 2005), but not always. Some results show that 1-MCP treatment can increase ethylene production in fruits, such as avocado (Jeong et al 2003;Hershkovitz et al 2005), banana (Golding et al 1998), graperfruit (Mullins et al 2000) and strawberry (Tian et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Samples from every treatment were taken at intervals for fruit firmness assay. Bars indicate standard deviation of the mean (n = 6) Plant Growth Regul (2009) 57:185-192 187 inhibited by 1-MCP (Fan et al 1999;Dong et al 2002;Ergun et al 2005), but not always. Some results show that 1-MCP treatment can increase ethylene production in fruits, such as avocado (Jeong et al 2003;Hershkovitz et al 2005), banana (Golding et al 1998), graperfruit (Mullins et al 2000) and strawberry (Tian et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The application of aminoethoxyvinylglycine, an ethylene synthesis inhibitor, and of diazocyclopentadiene, an ethylene action inhibitor, has shown that the biosynthesis of ester volatiles by ripening apples requires not only continuous ethylene action, but also a high rate of ethylene production [12]. Another inhibitor of ethylene action, 1-methylcyclopropene, also prevented the production of volatiles that contribute to apple aroma [43], although it is unclear whether the production of all volatile compounds was inhibited to the same degree [14].…”
Section: Apple Fruitsmentioning
confidence: 99%
“…Antisense suppression of the key ethylene biosynthesis genes showed impacts on ripening related processes (Defilippi et al 2005). Apples treated with the ethylene action inhibitor 1-methylcyclopropene (1-MCP) soften slowly and have reduced internal ethylene concentration relative to untreated fruit (Fan et al 1999;Watkins et al 2000;Defilippi et al 2004). Suppression of the biosynthesis of this gaseous hormone is one of the mechanisms by which controlled atmospheres extend the storage life of apples (Gorney and Kader 1996).…”
Section: Introductionmentioning
confidence: 99%